POLA KOMUNIKASI KOMUNITAS RUMAH KUCING RESCUE DALAM UPAYA PENYELAMATAN KUCING-KUCING TERLANTAR DI KOTA PEKANBARU - ", Yulika; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Animal abuse or cruelty to animals, especially cats is a thing that is currently happening a lot, the background of people doing animal abuse is usually based on feelings of annoyance at animals because they do not hurt humans, for example by beating and burning even if someone consumes the meat of the animal. Based on data obtained from the Pekanbaru City Animal Husbandry and Health Office, there are at least 30 cases per day in terms of violence and beatings of cats and dogs in the city of Pekanbaru. Related to this, the Rescue Cat House Community as a community that cares for animals, especially cats, seeks to save abandoned cats in the city of Pekanbaru.This study uses a qualitative descriptive research method, with the location of the study in the field. Hangtuah the tip of Pekanbaru City. The research subjects consisted of 3 informants who were selected through purposive techniques. Data collection is done through interviews, observation, and documentation. To determine the validity of the data the author uses the method of extension of participation and triangulation.The results of the research obtained indicate that the community communication flow of Rumah Kucing Rescue uses one-way and two-way communication. activities such as rescue processes, treatment and care programs, and other RKR activities, all members can convey and explain information or messages between each other regardless of status in the community but still have courtesy and mutual respect. The communication network that is carried out is the pattern of all channels, namely communication of all channels in the Pekanbaru Rescue Cat House community occurs when the chairman, management, and other members can communicate with each other face-to-face during meetings, run programs, or while conducting other activities, all members are the same and all also have the same power to influence other members. The form of activities carried out by the Rumah Kucing Rescue community in an effort to save abandoned cats in the city of Pekanbaru include family gatherings to establish intimacy among members, Facebook media partners in disseminating information regarding RKR, car free day (CFD), open donations, and bazaar.Keywords: Communication patterns Community Rescue Cat House